Measuring collective competencies of organisations - a systematic review of literature - Zibell, Laurent (Cranfield University, 2007)
The present Systematic Review explores the existing academic literature on the instruments to measure collective competences of organisations. The purpose is to identify those that could be further used in a PhD work on the competences of organisations involved in co-operative R&D projects. This area of research is at the intersection of Strategic Management, Human Resources Management, Evolutionary Economics and Business Performance Measurement. The methodology starts with a set of keyword strings for search in bibliographic databases. The extracted articles were then filtered for relevance and quality according to pre-defined criteria. An expansion of the resulting list was performed using cross-referencing and citation analysis. The final core list contains 33 articles. Descriptive statistics illustrate an emergent and highly fragmented field: the number of articles in the list rises sharply over the last 25 years, but no agreement is reached on either the nature of the variables to measure nor on the means to do so. The understandings of the concept of competence either aim at classifying firms (in a minority of articles), or at ranking them. In the latter case, the concept is assimilated to the proximity to best practices, to an efficiency or to an effectiveness in reaching functionally defined goals. Four families of methods are used in the existing literature to measure collective competences of organisations: questionnaires, exploitation of secondary data, case studies and interviews, in descending order of frequency in the core list. The selected articles provide a set of relevant concepts, of methods, of constructs, of third-party quantitative metrics and of individual questionnaire items useful for the further research.